2003
DOI: 10.1055/s-2003-38485
|View full text |Cite
|
Sign up to set email alerts
|

New Adjacent Bis-Tetrahydrofuran Annonaceous Acetogenins fromAnnona muricata

Abstract: Bioactivity-guided fractionation led to the isolation of two new Annonaceous acetogenins, annocatacin A ( 1). and annocatacin B ( 2). from the seeds and the leaves, respectively, of Annona muricata. Compounds 1 and 2 are the first examples where the adjacent bis-tetrahydrofuran ring system is located at C-15. The new structures were elucidated and characterized by spectral and chemical methods. Both Annonaceous acetogenins 1 and 2 showed significant in vitro cytotoxicity toward the human hepatoma cell lines, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 18 publications
1
34
0
6
Order By: Relevance
“…In addition, A. muricata leaf extract possesses antioxidant (Baskar et al,2007) and molluscicidal properties (Santos & Sant`Ana, 2001;Luna et al, 2006). Recent studies also showed anti-infl ammatory and analgesic properties in the leaves of the plant (Roslida et al, 2010;De Sousa et al, 2010) Among the chemical constituents found in the leaf of A. muricata are alkaloids (Le Bouef et al, 1981;1982), essential oils (Pélissler et al, 1994;Kossouh et al, 2007) and acetogenins (Wu et al, 1995a;1995b;1995c;1995d;Zeng et al, 1996;Chang et al,2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, A. muricata leaf extract possesses antioxidant (Baskar et al,2007) and molluscicidal properties (Santos & Sant`Ana, 2001;Luna et al, 2006). Recent studies also showed anti-infl ammatory and analgesic properties in the leaves of the plant (Roslida et al, 2010;De Sousa et al, 2010) Among the chemical constituents found in the leaf of A. muricata are alkaloids (Le Bouef et al, 1981;1982), essential oils (Pélissler et al, 1994;Kossouh et al, 2007) and acetogenins (Wu et al, 1995a;1995b;1995c;1995d;Zeng et al, 1996;Chang et al,2003).…”
Section: Introductionmentioning
confidence: 99%
“…According to Parbha Pathak et al, (2010) most susceptible bacteria was K. pneumoniae with Annona muricata leaves extract. Isolation of two new Annonaceous acetogenins, annocatacin A and annocatacin B from the seeds and the leaves which is proved to be which showed in-vitro cytotoxicity towards human hepatoma cell lines (Chang et al, 2003). The plant possess the major pharmacological activities includes cytotoxic, antileishmanial, wound healing, anti-microbial activity (Geetalaxmi et al, 2012).…”
Section: Picture1 and 2 Photographs Of Annona Muricata (Leaves And Fmentioning
confidence: 99%
“…Sirsak (Annona muricata L.) adalah salah satu tanaman yang bermanfaat untuk mengatasi berbagai penyakit. Hasil riset menunjukkan bahwa sirsak mampu menyembuhkan sakit jantung, asma, masalah liver (hati), dan rematik (Widyaningrum, 2011) serta mampu menyembuhkan berbagai kanker maupun tumor (Adewole, 2006;Chang, 2003;Wu et al, 2001). Hal ini dimungkinkan karena sirsak mengandung tanin, alkaloid, dan flavonoid (Kardinan, 2004).…”
Section: Pendahuluanunclassified